The generation of the utopia: Itinerant curriculum theory towards a 'futurable future'. Issue 3 (4th May 2022) - Paraskeva, João M.
ABSTRACT: Drawing on Pepetela's novel The Generation of Utopia, the article situates and dissects the role of a group of intellectuals within a radical critical curriculum river, working towards a more just society and education, and enhancing a utopian generation. The article emphasizes the erroneous persistence of intellectuals associated with such generation in working fundamentally within a Modern Western Eurocentric platform; it underlines how the battles between dominant and counter-dominant traditions could not avoid the epistemicidal nature of the curriculum and drove the field into a theoretical involution, a regression. The paper argues for the need to decolonize Modern Western Eurocentric counter-dominant approaches; and advances the itinerant curriculum theory, as a just approach to champion the struggle against the curriculum epistemicide – a decolonial turn. The article ends calling for 'the death' of traditional ways to produce critical theory – Eurocentric fully saturated – as a way to de-link the critical theoretical out of the coloniality matrix, and in so doing, honoring the rich legacy of the generation of utopia.